Relational Understanding in Solving Mathematical Problems: A Systematic Literature Review - Mefiana, Syifa Ananda; Juandi, Dadang (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Relational understanding is the ability to apply and relate one material to another and know the reason. The purpose of this research is to conduct a study related to relational understanding in solving mathematical problems at the elementary, junior high, junior high, high school and university levels. This study used the systematic literature review (SLR) method, with a sample of 21 research results related to relational understanding in solving mathematical problems published within the last nine years. Data collection was carried out by documenting all research related to relational understanding in solving mathematical problems in terms of research year, publication platform index, education level, research demographics, research type and research results. The results showed that the most years of related publications were in 2022, the dominating participants were at the junior high school level, Java Island as one of the largest populations was the most frequent location for research and qualitative research was the type of research often used by researchers with mixed results depending on students' initial mathematical abilities, learning styles, cognitive or non-cognitive styles of students and effective learning methods used to improve relational understanding.